Wireless sensor system untuk pengukuran daya listrik panel surya - Yurixa Sakhinatul Putri; Suryono Suryono; Jatmiko Endro Suseno (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
In this research, wireless sensor system is used to electrical power of solar cell measurement with wirelessly through of WiFi as data transmision. This system is required to monitoring and measuring electrical power of solar cell with long distance. This system also very helpful personil to do measurement because could be solving a problem in personnel limitations and instrument limitations. So, wireless sensor system become a solution in measurement. The system is made from voltage sensor circuit and current sensor circuit. Sensors are connected to ADC ATSAM3X8E microcontroller. Microcontroller reads voltage and current values by converting the analog scale to digital for sent to computer. Then, the data was saved in database and was sent to central station. Data has sent wirelessly by WiFi which is could be shown via web browser on computer. The result of calibration voltage sensors has correlation 0.9885 to standard gauge and average error 0.013 volts. The result of calibration current sensor has correlation 0.9881 to standard gauge and average error 0.012 ampere. The result of comparison beetween data which is sent from the field and received data has 0% error. So, it could be say that there is no placement data error.Keywords: Wireless Sensor System, Electrical Power, Solar Cell, Measurement, WiFi